In defense of a general right to equality - Borowski, Martin (2025)
This article examines the various forms that the right to equality takes in national and international provisions, distinguishing between those of an “ancillary” nature - which protect against discrimination only in relation to certain recognized rights - and those of “general application,” which cover all state acts. Based on this classification, it argues that both closed and open lists of prohibited criteria have limitations in guaranteeing comprehensive protection. In response to this, it raises the need for a general right to equality, the existence of which is implicit, for example, in Article 24 of the American Convention on Human Rights (ACHR). Through an analysis of the German system, particularly Article 3 of its Basic Law, it is justified how this general right offers a broader and more effective framework for assessing equality and combating discrimination that falls outside traditional lists. It is argued that a consistent interpretation of the ACHR implies recognizing the general dimension of the right to equality, thus overcoming the limits of accessory prohibitions. This would strengthen legal protection against unjustified treatment, promoting a more robust human rights framework in national and international contexts.